Role of Paediatricians in Paediatric Ophthalmology - Shrestha, Ujjowala Devi (Journal of Nepal Paediatric Society, 2013)
Children are primarily examined by paediatricians. In Nepal, child health is in low priority due to illiteracy, there is total lack of awareness about children’s eye health. The common avoidable causes of childhood blindness are refractive errors, amblyopia, retinopathy of prematurity (ROP), vitamin A deficiency (VAD), xerophthalmia, ophthalmia neonatorum (ON), congenital cataract, and retinoblastoma. Paediatricians could be the key persons for early referral of these children to a paediatric ophthalmologist. Paediatricians can send the patients for eye examination after birth within 6 weeks, at 6 months, at one year and before going to school. In conclusion, early screening and referral by the paediatricians to the paediatric ophthalmologist prevents children from being sightless. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7605 J Nepal Paediatr Soc. 2013;33(1):80-82